Bedugul Portrait: An Ethnoecological Study of the Relationship Between Man and the Environment - Wawan Sujarwo (Department of Urban and Regional Planning, Diponegoro University, 2019)
Bedugul is situated in the highlands of Bali, combining panoramic views of hills, forests, and lakes. Today, Bedugul has transformed from a remote area into a favorite tourist destination. Also, Bali has become one of the world’s leading tourist destinations, and this represents a suited model to study the influence of recent modernization, the tourist industry, population increase, and agricultural practices on traditional ecological knowledge (TEK). At the same time, few scientific references discuss Bedugul in term of TEK. Therefore, this study aims to present the latest portrait of Bedugul community in the millennial era and its relationship with the surrounding environments. A total of 20 Bedugul locals were interviewed. The selection of respondents was purposive, representing various Hindus and Moslem communities, with variations in age range (25-60 years old), gender, and occupation. The data were then analyzed through a qualitative descriptive approach with in-depth discussion. The results of the study showed that the Bedugul landscape has a strong cultural and ecological relationship with its communities, i.e., Hindus and Moslems. People activities in the natural areas of Bedugul, i.e., Batukahu Nature Reserve, are still in the normal stage. Most of Bedugul communities strongly depend on agricultural and tourism sectors. Land-use changes (human settlements, tourism facilities, and agricultural land) and the increasing population growth have resulted in the carrying capacity of Bedugul area becoming very vulnerable, and one of them is the emergence of pest species. The negative impacts of agricultural and tourism activities have been identified, some of which were using inorganic pesticides in high-doses, traffic congestion, and Lake Beratan water pollution due to restaurant waste and speed boat oil spills. This may result in the decline of local values within the Bedugul communities. This study concluded that erosion of traditional ecological knowledge, including ethnobotanical knowledge, is at risk of increasing.